EFEKTIVITAS BIMBINGAN KELOMPOK MELALUI TEKNIK ROLE PLAYING UNTUK PENINGKATAN SELF AWARENESS PESERTA DIDIK (Jurnal Bimbingan dan Konseling Islam, 2015)
This research based on phenomenon an individual who had a lower level of awareness, felt anxious, insecure, always blaming others, less responsible and did not have the commitment to achieve the goals of their life. This study aimed to increase student’s self awareness through group guidance with role playing techniques. This research used a quantitative approach with quasi-experimental method pretest-posttest design non equivalent. Data was collected by self awareness questionnaires based on theory of Thomas Shelley Duval, Paul Silvia dan Neal Lalwani (2001) . Study participants were 30 students of XIIth grade  High School Laboratorium Percontohan UPI who had indicates lower self awareness categories and divided into experimental group  (8 M : 8 F) and  control group (7 M : 7 F). The research samples was done by using non probability sampling and used difference between two means Wilcoxon and Man Whitney technique analysis. The result showed that group guidance with role playing technique was effective to increase student’s self-awareness, because p value 0,002 < 0,05 (?).